PENGARUH PROMOSI DISKON DAN GRATIS ONGKIR SHOPEE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Geofakta Razali; Dessy Andamisari; Jun Saputra (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Shopee is one of the e-commerce sites in Indonesia, shopee is more focused on mobile platforms so that people can more easily access, search, shop and sell directly using only their cellphones. This study is intended to analyze the effect of shopee discounts and free shipping on consumer purchasing decisions on students of the 2018 Central Campus Communication Study Program. This study uses a survey method, using a questionnaire as a data collection instrument. In entering the sample using purposive sampling technique. As for the respondents, 92 people with the Stiami Institute Student Criteria for the 2018 Central Campus Communication Study Program, for data processing using the SPSS Version 26 program for windows. The result is that H1 is accepted because r count > rtable 3,603, so it can be ascertained that H1 is accepted which means there is a discount on purchasing decisions, H2 is accepted because r count > r table is 3,712 , so it can be said that H2 is accepted which means free shipping has an effect on buying decision Keywords: Shopee, Promotion, Discount, Free Shipment, Buying Decision